Valuing specialised property: cost vs profits method uncertainty. Issue 6 (5th September 2016) - Jansen van Vuuren, David
Abstract : Purpose: The purpose of this paper is to compare the value outcomes of the cost approach to the DCF profits method when valuing specialised property under different scenarios as a test for choice of method or model uncertainty; and to quantify valuation uncertainty under each scenario and to argue for an increasing adoption of the profits method of valuation. Design/methodology/approach: A qualitative case study approach was used to analyse four physical valuations performed in practice under four specific scenarios, namely, a business-as-usual scenario, an underperforming business scenario, an expanding capacity scenario and a combined business-as-usual funding a start-up joint venture scenario. Findings: The cost approach relative to the DCF profits approach consistently under-values specialised property under business-as-usual and business expanding scenarios while it over-values in instances of underperforming business scenario. Practical implications: Financial institutions that predominantly uses or accepts the cost approach for valuing specialised property should consider adopting the DCF profits approach as the default approach when valuing for mortgage lending purposes. Business owners of specialised properties should contract practitioners knowledgeable and skilled in the application of the DCF profits method. Originality/value: This paper quantifies choice of method or model uncertainty of four different scenarios of specialised properties where both the cost approach and DCF profits methods of valuation were employed. It suggests the adoption of the DCF profits method as the default method of valuation for specialised property.